Work-Family Conflict, Life-Cycle Stage, Social Support, and Coping Strategies among Women Employees - Ahmad, Aminah (2007)
This study examined the work-family conflict experienced by 239 married female production operators in dual-career families, the social support they received and the coping strategies used to manage the conflict. The women experienced more work interference with family than family interference with work. The intensity of work interference with family was significantly higher in the earlier life-cycle stage than in the later stage. About two thirds of the women indicated that they intended to leave their job upon having another child, mainly due to the rising cost of childcare services. They received the least social support from their supervisors compared to other sources, and tended to cope with conflict using reactive role behaviour and personal role redefinition strategies.